Utilization of technology as a strategic tool for developing BPRS in North Sumatra in the digital era - Yanti, Tri Auri; Sugianto, Sugianto; Ramadhan, Muhammad; Yafiz, Muhammad (al-Uqud : Journal of Islamic Economics, 2025)
This study examines the use of technology as a development strategy for Islamic Rural Banks (BPRS) in North Sumatra in the context of the digital era. Employing a qualitative approach, it explores the adoption of digital tools—including mobile banking, management information systems, and digital payment platforms—by six BPRS operating in the region. The findings reveal that while several BPRS have initiated digital transformation through the implementation of mobile banking applications, digital risk management systems, and integration with Islamic fintech, the extent of adoption varies significantly, largely influenced by each bank’s financial capacity and strategic orientation. Other institutions remain in the early stages of digital development. Despite these initial efforts, major challenges persist, including inadequate technological infrastructure, limited capital, and a shortage of skilled human resources. Furthermore, collaboration with fintech companies and the application of digital marketing strategies remain underutilized. This study underscores the need to strengthen technological infrastructure, enhance capital capacity, and invest in human resource development to improve the competitiveness of BPRS in an increasingly competitive Islamic finance landscape. The findings offer practical insights for BPRS management in formulating technology-driven development strategies and promoting financial literacy within North Sumatra's communities.